Blackwell's ordering and public information. - Campbell, Colin M. (Journal of Economic Theory, 2004)
We characterize a precise comparative static on welfare and the amount of public information in an economy under uncertainty. Results dating to Hirshleifer (Amer. Econom. Rev. 61 (1971) 561) have suggested that information can have negative value in such a setting, but counterexamples using competitive equilibrium outcomes have suppressed general results to this effect. We show that under the solution concept of implementable allocations, the negative relationship between more public information in the sense of Blackwell and welfare is fully general. Furthermore, Blackwell's ranking is necessary as well as sufficient to obtain our ranking, and hence ours provides an equivalent characterization of his ordering. © 2003 Elsevier Science (USA). All rights reserved.